Influência da gonadotrofina coriônica humana sobre a hemodinâmica de folículos pré-ovulatórios e desenvolvimento luteal em águas - Romano, Rafael Mide [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
In recent years the hCG, because of its biological LH-like action, has been studied not only to induce ovulation, but also as luteotrophic agent. Doppler ultrasonography is a technique that allows the hemodynamic evaluation of follicular and luteal tissue, in real time, providing important functional information about these structures. This study aimed to describe the hemodynamics changes of pre-ovulatory follicles and characterize the structural and functional development of the corpus luteum of mares treated with different doses of hCG, at different times of estrous cycle. In experiment 1, mares were treated with 750, 1500, 2500 IU of hCG or NaCl 0.9%, intravenously, on presence of pre-ovulatory follicle ≥35mm. Doppler US exams, to evaluate the follicle vascular perfusion, were done every hour during first 12 hours post-treatment. Thereafter, it was done every 6 hours until ovulation. In experiment 2, treatment was performed with 750, 1500 or 2500 IU of hCG to induce ovulation, on the day of ovulation or two days post-ovulation. The luteal area, volume and vascular perfusion, and plasma progesterone concentration were evaluated daily from D0 to D8. No effect of dose and time was detected for follicle vascular perfusion. In experiment 2, there was no effect of dose and moment of treatment for all end points. Throughout the day, all end points presented significant difference, except the luteal area and volume. The hCG-treatment, to induce ovulation, did not increase follicle vascular perfusion post-treatment. hCG administered on the presence of follicle ≥35 mm, on D0 or on D2, had no positive influence on structural and functional development of corpus luteum, independent of dose

Nos últimos anos a gonadotrofina coriônica humana (hCG), por sua ação biológica semelhante ao hormônio luteinizante (LH), tem sido estudada não apenas como indutor da ovulação, mas também como agente luteotrófico. A ultrassonografia (US) Doppler, quando utilizada para análise ovariana, permite a avaliação hemodinâmica folicular e luteal, fornecendo importantes informações funcionais destas estruturas. Os objetivos deste estudo foram descrever as alterações hemodinâmicas de folículos pré-ovulatórios e, caracterizar o desenvolvimento estrutural e funcional do corpo lúteo (CL) de éguas tratadas com distintas doses de hCG, em diferentes momentos do ciclo estral. No experimento 1, éguas receberam 750, 1500, 2500 UI hCG ou NaCl 0,9%, por via intravenosa, na detecção de folículo pré-ovulatório ≥35 mm. A perfusão vascular (PV) folicular foi avaliada, por meio da US Doppler, a cada hora durante 12 primeiras horas pós-tratamento, e posteriormente, a cada 6 horas até ovulação. No experimento 2, foram utilizadas 750, 1500, 2500 UI hCG, para induzir ovulação, no dia da ovulação (D0) ou dois dias pós-ovulação (D2). A área, volume, PV luteal e concentração plasmática de progesterona (P4), foram avaliadas diariamente entre D0 e D8. Não foi detectado efeito da dose, do tratamento e tempo para PV folicular. No experimento 2, para todas as variáveis, não observou-se efeito da dose e tratamento, no entanto, ao longo dos dias, houve diferença significativa, exceto para área e volume luteal. A hCG, para induzir ovulação, não alterou a PV folicular pós-tratamento. Quando utilizada para induzir a ovulação, no D0, ou D2, não influenciou o desenvolvimento estrutural e funcional luteal, independente da dose
Keywords: Egua - Reprodução; Ovulação; Corpo lúteo; Doppler, Ultrassonografia; Ovulation